Decision Support System for Selecting the Best Raw Material Supplier Using Simple Multi Attribute Rating Method Technique - Raditya Rimbawan Oprasto (Jurnal Ilmiah Computer Science, 2023)
Problems that occur in the selection of raw material suppliers There is no assessment process for raw material suppliers based on the performance of these suppliers, so that companies cannot choose which suppliers best match the criteria used based on the performance of raw material suppliers for the company. This study aims to carry out the selection of raw material suppliers using a decision support system model by utilizing the SMART method in supporting decision making, so that the ranking results provide recommendations for companies in choosing raw material suppliers to be selected by companies based on the decision support system model made. The Simple Multi Attribute Rating Technique method is a simple but effective approach in making multi-criteria decisions. With a focus on assessing and comparing alternatives based on a number of criteria, SMART provides an intuitive framework to overcome the complexity of choosing the best option. The ranking results based on the table above Vendor C with a final score of 0.735 getting rank 1, Vendor D with a final value of 0.588 getting rank 2, Vendor B with a final score of 0.5 getting rank 3.